The COVID-19 pandemic and its potential enduring impact on children. Issue 1 (February 2022) - Irwin, Margaret; Lazarevic, Bojan; Soled, Derek; Adesman, Andrew
Abstract : Purpose of review: The COVID-19 pandemic has ushered in great and rapid change in our society. Although children are somewhat less likely to get infected or have severe symptoms from COVID-19, they are being adversely affected by this global public health emergency in many direct and indirect ways. This review focuses on the major areas in which children and adolescents are suffering, and how pediatricians can anticipate and optimize child healthcare and support as the COVID-19 pandemic and its aftermath continues. Recent findings: This review provides preliminary insights into the physical, psychological, educational, developmental, behavioral, and social health implications of the pandemic on the pediatric population, highlighting both the pandemic's current and potential future impact on children. Summary: The COVID-19 pandemic has and will likely continue to adversely affect many different aspects of children's health and well-being. It is important for pediatricians to be aware of these consequences of COVID-19 and take steps to help their patients now and in the future. Because the virus continues to ravage many parts of the world, continued research is needed to identify and evaluate any additional COVID-related challenges and concerns that adversely impact the growth and development of children.